Renaissance poetry in print and the role of Marin Držić - Šporer, David (Primerjalna književnost, 2012)
The paper proposes that the first printed edition of selected plays and the collection of poems by Marin Držić from 1551 played a pivotal role in emancipating the printing of poetry in Renaissance Dubrovnik and the broader context of the Croatian Renaissance in a process similar to processes in other cultures at the time.
Keywords: Držić, Marin, 1508-1567; hrvaška književnost; literarna zgodovina; history of literature; renesansa; poezija; drama; dramatika; zgodovina tiska